The lived experience of osteoporosis in the male body : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Health Psychology at Massey University, Palmerston North, New Zealand - Kawakami, Sachiko (Massey University, 2010)
Introduction: Osteoporosis has been medicalised as primarily a women‟s disease, despite the fact that men are also at risk. Although more attention has been paid to men‟s health in recent years, we know little about men‟s experiences regarding being diagnosed with, and living with, osteoporosis. This study was undertaken to address this gap in knowledge and attempted to explore what osteoporosis might mean for masculine identity and ageing. The male body was theorised as the phenomenological body, embodied masculinity integrated with Simone de Beauvoir‟s critique of gender and framed in her theory of old age. Methods: In-depth individual interviews were undertaken with four voluntary male participants aged between 42 and 86 years old (mean age = 62), diagnosed with osteoporosis 2-6 years previously. Interviews explored their perspectives regarding their body after diagnosis, and how that relates to other aspects of embodied life, including body image, past views, relationships with others and everyday living. Data were analysed using an existential-phenomenological approach, drawing upon Beauvoir‟s philosophy. Three main themes emerged: body image, body sensation, and body action, all of which together represent embodiment. Results: The medical diagnosis and bone density scan image served for the male participants to reconstruct their body images as fragile (how easy it is to break bones). The men attributed their chronic back pain to osteoporosis after the diagnosis. This led to the restriction of physical activities that they thought of as risky for fractures, which in turn encouraged them to engage in regular exercise. Meanings ascribed to osteoporosis (femininity, fragility, ageing) challenged their masculine identities. Although the participants recognised their bodies as ageing, they worked to retain their unchanging age-less self identities which were linked to masculinity. Conclusions: Men, like women, reconstructed their body images as fragile after the diagnosis of osteoporosis. However, men endeavoured to sustain dominant versions of masculinity by actively engaging in regular exercise and gendered roles. Findings have implications for health practitioners. Younger men may experience stigma with the construction of a feminised and aged disease. Gender sensitive health promotion and health services can be achieved by understanding the psychological consequences men experience following the diagnosis of osteoporosis.
Keywords: Osteoporosis; Men; Health psychology; Masculine identity; Embodiment; Existential-phenomenological analysis; Simone de Beauvoir